13 bankers : the Wall Street takeover and the next financial meltdown - Johnson, Simon, 1963- (Vintage Books, 2011)
Provides historical context for the 2008 financial crisis and proposes a radical solution, the megabanks deemed "too big to fail" must be made smaller.--